Design and control of an automatic cable-cutting machine with the implementation of a stepper control program using PLC - Prayogo, Haris; Hartayu, Ratna (Gema Wiralodra, 2023)
Proper control design will reduce energy losses and production costs for the industry. Control system design also reduces the role of humans in production. An automatic cable-cutting control system can reduce cable manufacturing time so that a company's human resources do not need to carry out the cable-cutting process manually. This cable cutter uses a PLC for its central control, which will convert the length value into the number of pulses and calculate the number of cables to be cut. The HMI inputs the length of the cable to be cut and the number of cables to be missed. The stepper motor is used to run the cable-pulling mechanic, which will pull according to the size stated on the HMI. This system can cut AWG20 and AWG16 cables in various lengths from 50 mm to 3000 mm with the number or number of wires that can be set from 1 cut to 10 cuts for each size.